A brief history of time - Hawking, Stephen (Bantam Books, 1998)
In the ten years since its publication in 1988, Stephen Hawking's classic work has become a landmark volume in scientific writing, with more than nine million copies in forty languages sold worldwide. That edition was on the cutting edge of what was then known about the origins and nature of the universe. But the intervening years have seen extraordinary advances in the technology of observing both the micro- and the macrocosmic worlds.